Αντιμετώπιση προβλημάτων της καθημερινής ζωής: Η περίπτωση της παιδικής μοναξιάς - Γαλανάκη, Ε.; Η. Γ. Μπεζεβέγκης (Psychology: the Journal of the Hellenic Psychological Society, 1996)
The present study was part of a broader research prograrn of the first author concerning loneliness and coping behaviour in childhood. We attempted to explore children's definitions of loneliness as well as the kind and frequency of coping strategies children employ in order to deal with loneliness. 238 4th- and 6th-grade pupils answered the questions: 'What is loneliness?' and 'When you feel lonely, what do you do in order to stop feeling that way?'. Children defined loneliness as the sad feeling caused by the absence of friends and by peer rejection. Children used various coping strategies, including seeking the companionship of important others (e.g., parents, siblings, grandparents, peers, pets); solitary play; indoor and outdoor activities (e.g., television, video games, sports); cognitive strategies (e.g., attempt to forget this feeling, attempt to improve oneself in order to find friends and not being rejected by peers); and passive ways of coping (e.g., doing nothing, crying, going to sleep). The two most frequent strategies were seeking companionship in peers and watching television. Results are discussed in terms of age and gender differences and of their relevance to coping taxonomies known from relevant literature.